Experimental and numerical studies on prestressed concrete box girders strengthened with PVA-ECC and external prestressing - Haoran Guo; Jing Yang; Caiqian Yang; Fu Xu; Kai Jin (Case Studies in Construction Materials, 2024)
To improve the shear capacity and repair shear cracks in prestressed concrete box girders, a novel strengthening method utilizing Polyvinyl Alcohol-Engineered Cementitious Composite (PVA-ECC) was proposed and studied. The integrated method consisted of section enlargement with PVA-ECC and decentralized prestressing using prestressed steel strands, which were embedded in the PVA-ECC after being prestressed and bonded. Field investigations were conducted to study and evaluate the effectiveness of this method under random traffic loads using health monitoring systems. Additionally, based on engineering practices, three finite element models (unreinforced box girder, box girder with strengthened side web only, and box girder with strengthened entire web) representing different construction sequences were established to investigate changes in shear behavior before and after strengthening. Finite element analyses were conducted under various loading conditions, and the results showed that the stress response of the webs decreased by approximately 30–40 % after strengthening. Additionally, the deflection of the top slab decreased by approximately 25–35 %. The results from monitoring data and finite element analyses demonstrated that the proposed strengthening method effectively enhanced the shear performance of the box girder webs. This research can provide a reference for strengthening and evaluating existing prestressed concrete box girders.